Quaternary Ammonium Leucine-Based Surfactants: The Effect of a Benzyl Group on Physicochemical Properties and Antimicrobial Activity - Diego Romano Perinelli; Dezemona Petrelli; Luca Agostino Vitali; Giulia Bonacucina; Marco Cespi; Driton Vllasaliu; Gianfabio Giorgioni; Giovanni Filippo Palmieri (MDPI AG, 2019)
Quaternary ammonium amphiphiles are a class of compounds with a wide range of commercial and industrial uses. In the pharmaceutical field, the most common quaternary ammonium surfactant is benzalkonium chloride (BAC), which is employed as a preservative in several topical formulations for ocular, skin, or nasal application. Despite the broad antimicrobial activity against Gram-positive and Gram-negative bacteria, as well as fungi and small enveloped viruses, safety concerns regarding its irritant and cytotoxic effect on epithelial cells still remain. In this work, quaternary ammonium derivatives of leucine esters (C10, C12 and C14) were synthesised as BAC analogues. These cationic surfactants were characterised in terms of critical micelle concentration (CMC, by tensiometry), cytotoxicity (MTS and LDH assays on the Caco-2 and Calu-3 cell lines) and antimicrobial activity on the bacterial species Staphylococcus aureus and Enterococcus faecalis among the Gram-positives, Escherichia coli and Pseudomonas aeruginosa among the Gram-negatives and the yeast Candida albicans. They showed satisfactory surface-active properties, and a cytotoxic effect that was dependent on the length of the hydrophobic chain. Lower minimum inhibiting concentration (MIC) values were calculated for C14-derivatives, which were comparable to those calculated for BAC toward Gram-positive bacteria and slightly higher for Gram-negative bacteria and C. albicans. Thus, the synthesised leucine-based quaternary ammonium cationic surfactants can potentially find application as promising surface-active compounds with antimicrobial activity.